A prospective study to evaluate the efficacy of 11-13+6 weeks anatomy scan in detecting fetal structural anomalies compared to traditional 18-22 weeks scan - Elamaran, Elavarasi; Daniel, Saley; A. N., Regi George (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Congenital anomalies are one of the leading causes of infant mortality. Traditional TIFFA scan done at 18-22 weeks leads to delay in diagnosis, referral and management. With high resolution ultrasound and TVS probe, normal and abnormal fetal anatomy could be visualized in early gestation with good accuracy. Objective of present study was to evaluate the efficacy of 11-13+6 weeks anatomy scan in detecting fetal structural anomalies compared to traditional 18 -22weeks scan and in visualizing the complete normal fetal anatomy Methods: An Observational study of 300 antenatal patients at Jubilee Mission Medical College for 1 year (Jan-Dec2014) was done. The scan was performed at 11-13+6 weeks by TAS first, if a full fetal anatomy survey not achieved, TVS added. A mid-trimester fetal anatomy scan was then performed in patients who had not dropped out, miscarried or undergone pregnancy termination at 18-22weeks. Results: The incidence of anomalies in our study was 3.67% -11 cases; 9 detected at 11-13+6 weeks, 2 were newly detected at 18-22 weeks. At 11-13+6 weeks anatomy scan, the detection rate of anomalies was 81.8% and complete fetal anatomy survey was achieved in 92%. Heart and kidneys were not properly visualized in 4% and 12.7%, at 11‐13+6 weeks compared with 0.7% and 0% at 18‐22 weeks. Conclusions: The 11-13+6 weeks anatomy scan is an important diagnostic tool which is underutilized and should be offered to all women as a routine standard of antenatal care. However as fetal anomalies can present at varying gestational age, standard 18-22 weeks anatomy scan cannot be abandoned.